Dynamics Simplification Strategy and Stability Optimization of 6-PTRT Parallel Manipulator - Xu Jing; Deng Zilong; Chen Hongjuan (Jixie chuandong)
The KANE dynamics equation of 6-PTRT parallel manipulator is derived according to the 6-PTRT parallel robot manipulator characteristic and pertinent literature. A tool in space surface processing trajectory is obtained by using quaternion form. The six degrees of freedom of the parallel robot is realized through space trajectory planning. The simplified strategy of the dynamics model is obtained to improve the operation efficiency by analyzing the influence of the moving parts on the driving force in middle and low speed and high speed machining. The cause of the fluctuation of the dynamic response curve of the mechanism is analyzed. In order to get a more smooth dynamic response curve,the Akima interpolation method is used to optimize the dynamic response of each branch,so as to improve the stability of the mechanism. The research provides the theoretical basis for the structure design,trajectory planning and real time control.